Glacial landforms and river terraces in the thakkhola regions, central Nepal - Iwata, Shuji; Yamanaka, Hidetsugu; Yoshida, Mitsuo (Journal of Nepal Geological Society, 1982)
In order to clarify the relationship between the river terraces and the glacial landforms, and the deformation of the river terraces, a series of field surveys was carried out in the upper course of the Kali Gandaki. Between Ghasa and Marpha, there are manyrried out in which were formed by the glaciers from the tributaries. These moraines dammed up the Kali Gandaki, and accordingly, conspicuous terraces are developed upstream. The Middle Terraces are considered to correlate with the Last Glacial age by the paleomagnetic measurements of the deposits at Kingar in the Muktinath basin. Along the kali Gandaki, the river terraces increases their relative heights above the river bed towards the Great Himalayan Range. This suggests that the uplift of the Great Himalayan Range have continued up to present.